Development of Snakes and Ladders Game for Physical Fitness Employees of PT Best Profit Medan 2020 - Jony Damanik; Tarsyad Nugraha; Suprayitno Suprayitno (Journal Physical Education, Health and Recreation, 2021)
This research was conducted at PT Best Profit Medan. The research treatment was carried out by adjusting the schedule during work holidays. The time of this research was carried out from October 2020 to November 2020. Subjects or users targeted in research on the development of the snake and ladder game on physical fitness for employees of PT Best Profit Medan. The issues in the small group in this study were 20 employees of PT Best Profit Medan, and the subjects in the large group in this study were 40 employees of PT Best Profit Medan. The research subjects were taken based on the purposive sampling technique with the following criteria: 1) for women in healthy body condition and not in a state of pregnancy, 2) for men whose body condition was healthy and did not suffer from internal diseases. This research method is a development method. The study results are small group product trials. From the value obtained, it is known that the empirical score obtained is 78.87% (Appropriate to Use), so it can be stated that the snake and ladder game product is effective. Large group trial, the results above are the results of the questionnaire distributed to the experts attached in the attachment and then calculated. The acquisition of the expert revision in the small group trial is 98.44% (Very Appropriate to Use), but in extensive group trial studies, it has been no revisions from experts.